2018
DOI: 10.1016/j.redox.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Sorting cells alters their redox state and cellular metabolome

Abstract: A growing appreciation of the metabolic artifacts of cell culture has generated heightened enthusiasm for performing metabolomics on populations of cells purified from tissues and biofluids. Fluorescence activated cell sorting, or FACS, is a widely used experimental approach to purify specific cell types from complex heterogeneous samples. Here we show that FACS introduces oxidative stress and alters the metabolic state of cells. Compared to unsorted controls, astrocytes subjected to FACS prior to metabolomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 36 publications
(38 reference statements)
4
128
1
Order By: Relevance
“…Yet, in contrast to previous reports (44,45), the cellular sensing was not accompanied by detectable cellular stress responses. However, other methods like detection of mitochondrial reactive oxygen species (mROS) stress responses (46) or inhibition of the p38 dephosphorylation by MAPK phosphatases (MKPs) might provide additional insights and therefore we cannot fully exclude minor sorterinduced cellular stress responses or an inhibition of the p38 dephosphorylation as cellular responses to sorting.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in contrast to previous reports (44,45), the cellular sensing was not accompanied by detectable cellular stress responses. However, other methods like detection of mitochondrial reactive oxygen species (mROS) stress responses (46) or inhibition of the p38 dephosphorylation by MAPK phosphatases (MKPs) might provide additional insights and therefore we cannot fully exclude minor sorterinduced cellular stress responses or an inhibition of the p38 dephosphorylation as cellular responses to sorting.…”
Section: Discussionmentioning
confidence: 99%
“…23 We also found that each plasma cell subset had mostly distinct immunoglobulin repertoires, were generated contemporaneously through the course of an NP-Ovalbumin (OVA) immunization, and showed similar expression of CD93, a marker of mature plasma cells, indicating that these subsets are formed independently of each other. 155 These cells recover after a rest period ex vivo. These data suggest an intrinsic ability of long-lived plasma cells to robustly import nutrients, rather than changes in the nutrient content in the local microenvironments of long-and short-lived plasma cells.…”
Section: Nutrient Uptake By Plasma Cellsmentioning
confidence: 99%
“…One technical caveat we have noticed anecdotally is that plasma cells assayed immediately after having been fluorescence activated cell sorted display very poor glucose import rates, perhaps due to stresses imposed by the process. 155 These cells recover after a rest period ex vivo. Given the minimal expression of known glucose transporters in mouse and human plasma cells, as-yet unknown genes and pathways likely promote extracellular sugar import.…”
Section: Nutrient Uptake By Plasma Cellsmentioning
confidence: 99%
“…Two recent studies showed that cell sorting can induce oxidative stress, altering the basal metabolic state of cells (17), and that the presence of photo-sensitive molecules within standard serum supplemented cell culture medium could drive morphological changes or cell death via oxidative stress (18). In each case, addition of serum or antioxidants reduced measurable cell stress.…”
Section: Discussionmentioning
confidence: 99%